IMPROVING TEACHER PROFESSIONAL DEVELOPMENT THROUGH DIGITAL TECHNOLOGIES IN UZBEKISTAN - Xudayberganova Ro’za Rasul qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
RELEVANCE OF THE TOPIC.In the era of globalization and the digital economy, the quality of the education system is directly dependent on the professional competence of teachers and their ability to operate within modern technological frameworks. Under the "Digital Uzbekistan — 2030" strategy, the digitalization of the educational sector has been identified as a national priority. However, traditional professional development systems often fail to address the individualized needs of educators or keep pace with the rapid flow of scientific innovations. Therefore, leveraging digital technologies to elevate teacher training to a new level and creating a continuous learning environment is highly relevant and necessary for the country’s development. OBJECTIVE.The objective of this research is to analyze the mechanisms of enhancing teacher professional development through digital technologies (LMS platforms, online courses, virtual communities) in the context of Uzbekistan and to develop practical recommendations to increase the efficiency of this process. INTRODUCTION.In modern pedagogy, the principle of LPL (Lifelong Professional Learning) is becoming a cornerstone of academic success. Today’s teacher must be more than a mere transmitter of knowledge; they must serve as a facilitator in the digital world. The transition to electronic systems for teacher certification and training in Uzbekistan (e.g., the on-line.uzedu.uz platform) represents a significant milestone. Digital technologies allow educators to access global best practices without being constrained by time or geography, fostering a culture of self-improvement and pedagogical innovation.